Line transect estimates of humpback whale abundance and distribution on their wintering grounds in the coastal waters of Gabon - Strindberg, Samantha; Ersts, Peter J.; Collins, Tim; Sounguet, Guy-Philippe; Rosenbaum, Howard C. (J. Cetacean Res. Manage., 2020)
There have been few recent estimates of abundance for humpback whales (Megaptera novaeangliae) in the eastern South Atlantic Ocean. The first distance sampling survey of the coastal waters of Gabon was conducted in 2002. The difficult logistics of covering a large survey region with limited time, effort and refuelling opportunities required a line transect survey design that carefully balanced the theoretical demands of distance sampling with these constraints. Inshore/offshore zigzag transects were conducted to a distance of up to approximately 50 n.miles from the coast of Gabon corresponding to the 1,000m depth contour, from the border with Equatorial Guinea to a point south of Mayumba, near the Congo border representing 1,488 n.miles of survey effort. Seventy-nine different groups of humpback whales were observed throughout the survey area comprising a northern (Equatorial Guinea to Cap Lopez) and southern (Cap Lopez to Gamba) survey stratum. Relatively large numbers of whales were encountered throughout the southern stratum; encounter rates and densities were considerably lower in the northern stratum. The initial abundance estimate from a distance sampling analysis suggests that more than 1,200 humpback whales were present in Gabon’s coastal waters during the survey period. This estimate does not account for either availability or perception bias. In addition, this instantaneous snapshot of the number of whales occupying Gabon’s coastal waters is likely to correspond to only a portion of the population that uses these waters over time. However, the abundance estimate derived from the aerial survey are consistent with those based on photographic and genetic capture-recapture techniques. A continuing research programme in this area will help refine estimates of humpback whale abundance and using genetic and photographic data also establish the relationships between this and other populations. This is important given the potential overlap of humpback whales in large numbers throughout this region and the current extent and continued expansion of hydrocarbon exploration and extraction activities throughout the Gulf of Guinea.